Comparison between merthiolate–iodine–formalin and Kato–Katz methods for the diagnosis of human helminth infections in resource-limited settings. Issue 6 (28th October 2016) - Incani, R.N.; Homan, T.; Pinelli, E.; Mughini-Gras, L.; Guevara, H.; Jesus, J.
Abstract: Diagnosis of intestinal parasites through examination of fresh faecal samples is hampered by its unpleasantness and the urgent need to detect all parasitic forms. In this paper, we compared the standard Kato–Katz (KK) technique with a traditional fixation method, the merthiolate–iodine–formalin (MIF) method. Two hundred and twenty-seven faecal samples from individuals living in a rural setting in Venezuela with high to moderate prevalences of Ascaris lumbricoides ( Al ), Trichuris trichiura ( Tt ) and hookworm infections were examined. The 'gold standard' used here was derived from the combination of the outcomes from both methods. KK performed better at detecting Tt, and showed higher sensitivity and negative predictive value for both Tt and Al, probably due to a higher capacity of KK to detect low parasite loads. Both methods showed an almost perfect agreement using the Kappa index. MIF provided a higher median of parasitic loads for low and total egg counts for the three helminths. Differentiating fertile from infertile eggs of Al did not affect the results; infertile eggs were present only at low and intermediate parasitic loads, but absent at high loads. KK was not able to detect high loads of any of the helminths. MIF allowed for the detection of other helminths, such as Strongyloides stercoralis, and protozoan infections, for which KK is not specific. In conclusion, MIF is a simple and inexpensive technique that performs competitively with KK in both laboratory and field work on intestinal helminths, particularly in resource-limited settings.